2009
DOI: 10.1007/s12094-009-0361-7
|View full text |Cite
|
Sign up to set email alerts
|

Bronchogenic carcinoma in patients under 50 years old

Abstract: In our series, despite the differences in sex, smoking history and histology, the behaviour of the disease is similar in both age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…This result is consistent with previous studies, which showed a bias toward females, non-smokers, and adenocarcinoma histology (2-7). There were several conflicting results that male (8) and smokers (6) were more prevalent, the severity of disease at presentation was not different (5), and squamous cell carcinoma was more frequently diagnosed than adenocarcinoma (4, 8). Furthermore, several studies have described similar overall survival in young and old patients with lung cancer (3, 6, 7), whereas, others have reported worse (4, 5) or better overall survival (2, 8) in young patients compared with old patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is consistent with previous studies, which showed a bias toward females, non-smokers, and adenocarcinoma histology (2-7). There were several conflicting results that male (8) and smokers (6) were more prevalent, the severity of disease at presentation was not different (5), and squamous cell carcinoma was more frequently diagnosed than adenocarcinoma (4, 8). Furthermore, several studies have described similar overall survival in young and old patients with lung cancer (3, 6, 7), whereas, others have reported worse (4, 5) or better overall survival (2, 8) in young patients compared with old patients.…”
Section: Discussionmentioning
confidence: 99%
“…There were several conflicting results that male (8) and smokers (6) were more prevalent, the severity of disease at presentation was not different (5), and squamous cell carcinoma was more frequently diagnosed than adenocarcinoma (4, 8). Furthermore, several studies have described similar overall survival in young and old patients with lung cancer (3, 6, 7), whereas, others have reported worse (4, 5) or better overall survival (2, 8) in young patients compared with old patients. The discrepancies might be due to the rare occurrence of lung cancer in young patients, differences in study designs enrolling surgically treated cases only or including unresectable cases, and age cut-off levels dividing young and old age groups, and differences in smoking habits, environments and ethnicity in the populations studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies concluded that young patients had a longer survival [10,12,13,[15][16][17][18], although the authors sometimes acknowledged that they received more aggressive treatment, others found a shorter survival [19], and many studies did not find any survival difference between young and older patients [9,14,[21][22][23][24]. However, these results cannot be compared because the cut-off used to define young patients varies from 40 to 50 years, and the populations included in these studies are heterogeneous, sometimes limited to non-small cell lung cancer (NSCLC) or adenocarcinoma or restricted to patients who underwent surgery.…”
Section: Introductionmentioning
confidence: 99%
“…8 According to these studies, the young patients are more commonly non-smoking females [9][10][11][12][13][14] with an advanced stage of adenocarcinoma and with a considerably lower incidence of squamous cell carcinoma. [10][11][12][13] Specific molecular and pathological features might be associated with lung adenocarcinomas arising in young, female non-smokers. Over the past decade, a plethora of data from genomic, mutational and proteomic profiling studies have led to the identification of additional molecular driver mutations in lung cancer.…”
Section: Introductionmentioning
confidence: 99%